Democracy and Democratization in Comparative Perspective : Conceptions, Conjunctures, Causes, and Consequences. - Møller, Jørgen (Democratization studies., 2012)
This book provides an introduction to democratic theory and empirical research on democracy and democratization. The book first examines conceptions of democracy from the origins in ancient Greece to the present day, then tracks when and where modern democracy has developed. On this basis, the book reviews the major debates and schools of thought dealing with domestic and international causes and consequences of democratization. Based on a systematic distinction between minimalist and maximalist definitions of democracy, the book provides a comprehensive and critical assessment of existing.